Response of winter wheat grain yield and water use efficiency to deficit irrigation in the North China Plain - Han, Huifang; Zhenxing Yan, Yujie Ren (Emirates Journal of Food and Agriculture, 2018)
Water resources in the North China Plain (NCP) are limited, so it’s in urgent need to optimize deficit by irrigation for sustainable winter wheat production in this area. Winter wheat grain yield (GY), contribution of dry matter (DM) remobilization to GY (CDMRG), and water use efficiency (WUE) were investigated in NCP. Compared with non-irrigation treatment, irrigated with 60 mm each at the winter wheat jointing stage (JS) and heading stage (HS) achieved reasonable winter wheat GY and WUE. Compared with irrigation with 120 mm only at JS and irrigation with 40 mm each at JS, HS, and milking stage (MS) of winter wheat, irrigation with 60 mm each at JS and HS provided the highest CDMRG, which resulted to the highest GY and WUE; this result was mainly due to a significant increase of the spike numbers (SN) per m2. The results suggest that in the NCP, in order to achieve reasonable GY and WUE, winter wheat should be irrigated with 60 mm each at JS and HS.